Mathematical modeling of pharmacokinetics and pharmacodynamics of losartan in relation to CYP2C9 allele variants - Babaev, Dmitry; Kutumova, Elena; Kolpakov, Fedor (Frontiers in Systems Biology, 2025)
Losartan is a selective angiotensin II AT1-receptor antagonist for the treatment of arterial hypertension and heart failure. It is converted to a pharmacologically active metabolite carboxylosartan (E-3174) in the liver mainly by CYP2C9 enzyme, a member of the cytochrome P450 superfamily. The gene encoding this protein is highly polymorphic: numerous single nucleotide polymorphisms that alter the enzyme function have been described in the literature. The most widespread CYP2C9 alleles are CYP2C9*1 (wild-type), CYP2C9*2, and CYP2C9*3. Here we performed mathematical modeling of the metabolism of orally administered losartan to E-3174 taking into account combinations of the most common CYP2C9 alleles. Next, using the previously created model of the human cardiovascular and renal systems, we demonstrated that the blood pressure response to losartan therapy in a cohort of virtual hypertensive patients depended on CYP2C9 allelic variants. Individuals with the CYP2C9*1/CYP2C9*1 genotype responded better to treatment than patients carrying CYP2C9*2 or CYP2C9*3 alleles. The results of the modeling can potentially be used for personalization of drug therapy for arterial hypertension.